Integrated effects of K and Na application on initial growth of eucalyptus seedlings submitted to water stress: water use efficiency, leaf gas exchange and 13C isotopic variation - Mateus, Níkolas de Souza (2019)
In Brazil, fertilizer application is one of the main factors for achieving high productivity in commercial Eucalyptus plantations, since it is frequently carried out in soils with low water availability and low chemical fertility. Potassium (K) is the most required macronutrients by the Eucalyptus plant, while sodium (Na), can partially substitute some physiological functions of K, influencing directly the plants water use efficiency (WUE). Thus, the present study aimed to evaluate, in a greenhouse conditions, the nutritional and physiological responses of three eucalypt genotypes contrasting to drought tolerance under combined effects of different water regimes and partial replacement of K by Na. Plant growth, nutrients concentration, gas exchange parameters (A-CO2 assimilation rate, gs-stomatal conductance, E-transpiration, WUE), chlorohpyl content, absorption and use efficiency (AE and UE, respectively), stomatal density in adaxial and abaxial surfaces (StdAD and StdAB), leaf water potential (w), leaf area (LA) and leaf carbon isotope composition (13C ) were measured. The low replacement of K by Na improved growth of Eucalyptus under different water supply conditions, except for root dry matter, which decreased with any Na supply. Besides that, there was a higher potential of replacement according to raised drought tolerance levels among genotypes. Water supply was the most limiting factor for the growth, characterizing the plants under drought by lower TDM, LA, Std, A, E, gs, WN and UEK, despite higher 13C and long time water use efficiency (WUEL). In general, plants supplied with low Na rate (up to 50 % of K-replacement) reduced the critical level of K without showing symptoms of K deficiency and providing higher growth than those Eucalyptus plants supplied only with K. Also expressed the ability to improve CO2 assimilation, Std, UEK and WUEL, maintaining leaf turgidity by reducing wN, with stomata partially closed, indicated by the higher values of leaf carbon isotope composition (13C ). The exclusive Na supply, which leads to K-deficient plants, besides the lower growth, are mainly characterized by lower values of 13C, WUEL, leaf K content and higher leaf Na content